Abu Ampas Tebu Pengurang Semen Dalam Paving - Kholiddien Tyas Jawara; Pramudya Fathoni Winalda Purnama; Olga Donny Prasetyo; Tomi Tristono (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2018)
Cement is a basic requirement that is always needed in the construction work. Every year the price of cement has increased. In this experimental study using ash waste bagasse to reduce the amountÂ  of cement in paving by substituting it. Variations in the composition of the addition of bagasse ash are 0%, 5%, 10%, 15%, 20%, 25% of cement volume and with a ratio of 1: 4, i.e., 1 cement and 4 sand. Based from the results of compressive strength analysis, water absorption, and density, the paving with a mixture of ash-bagasse gain of 5% is the best when compared to other mixtures. The result are a compressive strength of 34.63 MPa, the water retention capacity of 2.12% and the density of 1.39 gr / cm3. The paving with a mixture of 10% bagasse ash yielded a compressive strength of 33.84 Mpa, the water retention capacity of 2.23% and the density of 1.37 g / cm3, indicating that 10% ash addition had the same paving test results without the addition of ash bagasse. In SNI 03-0691-1996, paving with the addition of bagasse ash by 5% and 10% including as the paving of quality B.Â Keywords : ash of waste bagasse, paving, pozzolan.